Modelagem matemática da dispersão de poluentes atmosféricos em indústria siderúrgica no Ceará - Marques, Leonardo da Cunha (2017)
In the state of Ceará, the study of air pollution is incipient and still little explored, despite being a subject of great socioenvironmental importance due to the industrial growth observed in the last decades in the state. This growth causes impacts on the local atmosphere, increasing the concentration of pollutants and the risk to human health. Thus, there is a need to monitor the degree of air pollution and evaluate compliance with environmental legislation. The objective of this study was to analyze the dispersion regime of atmospheric pollutants emitted from a steel industry located in the Maracanaú Industrial District, through the use of mathematical modeling tools, analyzing compliance with environmental legislation. For this, multiple runs were performed with the ISC3 and AERMOD air quality models for the following pollutants: Particulate Matter (PM10), Sulfur Oxides (SOx), Nitrogen Oxides (NOx) and Carbon Monoxide (CO), leading factors such as meteorology and the effect of Building Downwash. It was observed that the maximum concentration limits, established by the Brazilian environmental legislation, are being respected for all pollutants studied. We also analyzed the effect of buildings on the dispersion of the pollutant plume by comparing the ISC3, ISC3-PRIME and AERMOD models. It was observed that the ISC3 overestimated the concentration values, while the other two models presented values ​​close to each other and lower than the ISC3 because both incorporated the effect of Building Downwash in the dispersion calculation. Finally, a minimum chimney height of 55 meters was obtained in order to eliminate the Building Downwash effect in the dispersion.